PENERAPAN STRATEGI DIRECTED READING ACTIVITY (DRA) UNTUK MENINGATKAN KEMAMPUAN SISWA DALAM MEMBACA PEMAHAMAN KELAS V SDN 003 PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Simanjuta, Delima (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is the low literacy pehaman students, it nini caused by: (1) the ability of students to understand the content of the discourse is still low, it can be seen that only a fraction of the number of students who were able to mention the basic ideas and explanatory discourse; (2) the difficulty of students to identify the views or mandate contained in a discourse, it is seen when asked to mention the views or mandate in the discourse of only one to two students who are able to mention properly; (3) the ability of students to infer the contents of a student discourse is still struggling, it is seen when asked to infer the content of a discourse is also only one or two students to infer the contents of a discourse well; and (4). The difficulty students find important sentences in a discourse, it is seen when given the task of daily tests, most students is difficult to answer. To overcome the lack of ability of the students' reading comprehension strategies writers apply DRA (Directed Reading Activity). This research is a class act who performed two cycles each cycle performed in two meetings. The research was conducted in SDN003 Pagaran Tapah Darussalam, the research subjects were students of class V with the number of 20 students. This study was conducted with four stages, namely: (1) planning; (2) the implementation of the action; (3) observation; and (4) reflection. Based on the survey results revealed that students' reading comprehension before action classical gained an average of 49.80, in the first cycle increased to 63.50, while the second cycle increased by an average of 86.00 with a classical high category.